2009
DOI: 10.1080/10903120802706104
|View full text |Cite
|
Sign up to set email alerts
|

The Hazards of Providing Care in Emergency Vehicles: An Opportunity for Reform

Abstract: The risk of occupational death is disproportionately high for emergency medical services (EMS) personnel, largely as a consequence of the high incidence of transportation-related fatalities. The purpose of this narrative review is twofold: to raise awareness in the EMS community by examining the various factors that contribute to vehicular EMS injuries and fatalities and to outline practical strategies for mitigating these risks to EMS professionals. This review describes three main categories of factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…140 Multiple randomized trials have shown that mechanical chest compression devices are not demonstrably better than optimized manual CPR. 141 However, these devices may have a role in reducing risks to EMS providers associated with performing manual compressions in a moving vehicle 142 or in facilitating emergent coronary angiography in a patient with ongoing cardiac arrest and a high likelihood of acute coronary occlusion. 143 Although the acceptance of regionalized approaches to systems of care and designated centers has increased, some EMS systems remain challenged by local concerns related to bypassing closer hospitals and the resultant loss in patient volume and case-mix index.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…140 Multiple randomized trials have shown that mechanical chest compression devices are not demonstrably better than optimized manual CPR. 141 However, these devices may have a role in reducing risks to EMS providers associated with performing manual compressions in a moving vehicle 142 or in facilitating emergent coronary angiography in a patient with ongoing cardiac arrest and a high likelihood of acute coronary occlusion. 143 Although the acceptance of regionalized approaches to systems of care and designated centers has increased, some EMS systems remain challenged by local concerns related to bypassing closer hospitals and the resultant loss in patient volume and case-mix index.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…In order to perform compressions at least one member of the ambulance crew must remain standing and un-restrained next to the victim. A systematic examination of ambulance crash data identified that travelling with emergency lights and sirens increases the risk of an accident and standing, un-restrained in the back of the ambulance vehicle as important risk factors for injury and death [54]. Ambulance crews may also sustain back strain injuries as a consequence of prolonged chest compression in cramped circumstances [55][56].…”
Section: Transportationmentioning
confidence: 99%
“…These ambulance personnel are at least 4 times more like to have a fatal or incapacitating injury than personnel that are restrained. Mechanical CPR also allows high quality CPR to be performed while the personnel are restrained, reducing risk to the crew, (27,28) and thereby saving valuable EMS resources. Finally, mechanical devices can improve cost effectiveness of EMS systems by reducing the number of personnel needed to be present during resuscitative efforts, since separate personnel are no longer needed to perform manual CPR.…”
Section: Cost Effectiveness Of Mechanical Cprmentioning
confidence: 99%